Successful cryoablation of ventricular extrasystoles originating from the vicinity of the left anterior fascicle - Takatsugu Kajiyama; Yusuke Kondo; Masahiro Nakano; Kazuo Miyazawa; Miyo Nakano; Tomohiko Hayashi; Ryo Ito; Haruhiro Takahira; Yoshio Kobayashi (Journal of Arrhythmia, 2020)
Abstract A 32‐year‐old male received catheter ablation of frequent ventricular extrasystoles (VEs). His electrocardiogram showed monomorphic VEs with an inferior axis and early precordial transitional zone. During electrophysiological testing, a 10‐pole catheter positioned in the left ventricular outflow tract recorded sharp pre‐potentials just before the ventricular activation during VEs as well as sinus beats. Three‐dimensional mapping was performed by annotating the sharp pre‐potentials to reveal that the earliest activation site was deemed to be close to the left anterior fascicle. A cryoablation catheter was introduced into the left ventricle and freezing for 240 seconds successfully eliminated the clinical VEs without any complications.